Clinical and ultrasound joint outcomes in severe hemophilia A children receiving episodic treatment in Indonesian National Hemophilia Treatment Center (Medical Journal of Indonesia, 2017)
Background: Recurrent joint bleeds leading to arthropathy is the main problem in severe hemophilia children. This study aimed to investigate joint status in severe hemophilia A children receiving episodic treatment in Cipto Mangunkusumo Hospital, Jakarta. Methods: A cross-sectional study was conducted in Cipto Mangunkusumo Hospital as Indonesian National Hemophilia Treatment Center on children (4–18 years) with severe hemophilia A, who previously received episodic treatment, with no history of inhibitor factor VIII. Hemophilia Joint Health Score was evaluated according to HJHS version 2.1 2011. Joint ultrasonography was done for six index joints (bilateral elbows, knees and ankles) using Haemophilia Early Arthropathy Detection with Ultrasound (HEAD-US) methods. Data of age of first joint bleed, number of target joints and inhibitor factor VIII were obtained from the Pediatric Hemophilia Registry and medical records. Results: There were 59 subjects aged 4 to 18 years. Twentynine out of 59 (49.2%) subjects experienced first joint bleed before of 2 years of age. The most common of joint bleeds was a right ankle. Mean total HJHS was 8.71±8.73. Subjects aged 4–10 years showed lower HJHS (4.6±3.7) as compared to subjects aged >10–18 years (12.3±10.3), p<0.001; 95% CI=4.9–13. Mean HEAD-US scores in subjects aged 4–10 years (18.7±5.6) was lower than in subjects aged >10–18 years (28±7.9), p<0.001, 95% CI= -12.9–-5.6. Conclusion: HJHS and HEAD-US scores of severe hemophilia A children receiving episodic treatment aged 4–10 years are lower compared to subjects aged >10–18 years, indicating more severe joint destruction in older children and progressivity of joint damage over time. It is important to start prophylactic treatment to prevent progressivity of joint damage.